Fadama Iii Project And Output Performance Of Agricultural Enterprises: An Empirical Evaluation - Inam, Uduakobong S.; Effiong, Etim Augustine (Archives of Business Research, 2017)
This paper evaluates the impact of the Fadama III Project on output performance of agricultural enterprises of the beneficiaries in Akwa Ibom State, Nigeria. The study employed the Survey method wherein Questionnaire was administered and interview held. Data collected were analysed using Tables, Percentages and Chi-Square (X2) statistical method. Findings revealed that Fadama III project impacted positively on the beneficiaries in Akwa Ibom State as it contributed to the increase in the output performance of beneficiaries. This further contributed immensely to increased access to finances and a remarkable increase in the income of the beneficiaries. The study recommends among others, that government, relevant agencies and stakeholders should sustain the Fadama III project to ensure food security in the society and also for the benefit of the rural poor who are mostly engaged in agricultural activities in order to increase their ouput and improve their incomes.